(untitled) (UNED Research Journal, 2019)
Long term vegetation studies of Costa Rican premontane humid forests (transition to dry forest) are scarce. Objective: to compare a protected and a degraded forest. Methods: between 2015 and 2016 (ten months), I analyzed woody vegetation structure and composition in Bosque Andrómeda (site N°1: 305 individuals, 29 families and 51 species) and Los Llanos de la Garita (site N°2: 76 individuals, 16 families and 18 species). I measured DAP>10cm in 20 plots per site (500m2 each). Results: the most abundant species were Guazuma ulmiforia, Anacardium excelsum and Calycophyllum candidissimum in Andromeda; and Enterolobium cyclocarpum; Bursera simaruba and Andira inermis in Los Llanos. The most frequent species in Andrómeda were Guazuma ulmiforia, Anacardium excelsum and Cedrela odorata; and, in Los Llanos, Enterolobium cyclocarpum, Bursera simaruba and Tabebuia rosea. The dominant species in Andromeda were Cedrela odorata; Pseudobombax septenatum and Enterolobium cyclocarpum; and, in Los Llanos, Enterolobium cyclocarpum, Ficus spp. and Guazuma ulmifolia. The diversity in Andromeda was (H) 3,22 and in Los Llanos 2,50; dominance (DSi) in Andromeda is 0,95 and in Los Llanos 0,89; evenness (J’) of 0,85 in Andromeda and 0,87 in Los Llanos. Bray- Curtis dissimilarity was 0,81 and Jaccard species 0,89. The nonparametric estimators (ACE, Chao 1, Chao 2, Jackknife 1, Bootstrap) in Los Llanos showed a richness value of 20 to 28 species and in Andrómeda of 59 to 111. Conclusion: the horizontal structure is different, but the similar floristic compositions between sites should facilitate future ecological restoration.